Amphetamine use by truck drivers in Brazil: general aspects (Saúde Ética & Justiça, 2002)
Various epidemiological studies have been performed to show the relationship between the use of amphetamines and motor vehicle accidents. Truck drivers in Brazil use stimulant drugs, known as “rebites”, to reduce fatigue and enhance their performance to achieve dead lines and schedules agreed with the companies. The aim of the present article is to contribute with information about amphetamines and how these psychoactive substances affect the drivers, mainly the truckers.